Transmission of ciprofloxacin resistance in Salmonella mediated by a novel type of conjugative helper plasmids - Kaichao Chen; Ning Dong; Edward Wai-Chi Chan; Sheng Chen (Emerging Microbes and Infections)
Ciprofloxacin resistance in Salmonella has been increasingly reported due to the emergence and dissemination of multiple Plasmid-Mediated Quinolone Resistance (PMQR) determinants, which are mainly located in non-conjugative plasmids or chromosome. In this study, we aimed to depict the molecular mechanisms underlying the rare phenomenon of horizontal transfer of ciprofloxacin resistance phenotype in Salmonella by conjugation experiments, S1-PFGE and complete plasmid sequencing. Two types of non-conjugative plasmids, namely an IncX1 type carrying a qnrS1 gene, and an IncH1 plasmid carrying the oqxAB-qnrS gene, both ciprofloxacin resistance determinants in Salmonella, were recovered from two Salmonella strains. Importantly, these non-conjugative plasmids could be fused with a novel Incl1 type conjugative helper plasmid, which could target insertion sequence (IS) elements located in the non-conjugative, ciprofloxacin-resistance-encoding plasmid through replicative transcription, eventually forming a hybrid conjugative plasmid transmissible among members of Enterobacteriaceae. Since our data showed that such conjugative helper plasmids are commonly detectable among clinical Salmonella strains, particularly S. Typhimurium, fusion events leading to generation and enhanced dissemination of conjugative ciprofloxacin resistance-encoding plasmids in Salmonella are expected to result in a sharp increase in the incidence of resistance to fluoroquinolone, the key choice for treating life-threatening Salmonella infections, thereby posing a serious public health threat.